Dyadic Coping Pada Penderita Lupus Dan Pasangannya Di Komunitas Persatuan Lupus Sumatera Selatan (PLSS) - Laila Mujianti; Ema Yudiani (Indonesian Journal of Behavioral Studies, 2021)
This research aims to understand Dyadic Coping in Lupus sufferers and their partners in the Lupus community of South Sumatra. This study uses a qualitative research methodology with a descriptive design. Based on the findings, it can be concluded that both couples consisting of four subjects can interpret Dyadic Coping as an effort to help each other in dealing with stressful situations along with maintaining cooperative relationships in the household. This harmony is expressed by the couples through helping neglected work, as well as finding solutions to the source of stress that is got and helping in terms of emotional and spiritual things.